Development of Android-based applications integrated with Tari Piring culture as ethnomathematics learning media for elementary school students - Rachman, Kufita; Pangestika, Cahya; Vesya, Siti Raihani; Arbiyanti, Ade Putri (UNION : Jurnal Ilmiah Pendidikan Matematika, 2025)
Technology-based learning must be developed to create interactive learning experiences that enhance students' motivation and understanding of the material. This study aims to develop an Android-based application integrated with Tari Piring as an ethnomathematics learning tool for fourth-grade elementary school students. The subjects of this study were fourth-grade students of SD Negeri Golo. The research method used is the Research and Development (R&D) approach, following the 4-D model, which consists of four stages: defining, designing, developing, and disseminating. Data collection was conducted through interviews and questionnaires. The interview data were analyzed descriptively, while the questionnaire data were analyzed using descriptive statistics. The developed Android-based application received an average score of 3.85 from material experts, with a feasibility percentage of 96.25%, categorizing it as highly feasible. Similarly, media experts provided an average score of 3.85, also with a feasibility percentage of 96.25%. Meanwhile, the practical assessment based on student responses yielded an average score of 3.7, which falls into the applicable category with a percentage of 93%. In conclusion, the Android-based application integrating Tari Piring in ethnomathematics learning is effective for teaching geometric concepts to elementary school students. This research contributes to the advancement of technology-based ethnomathematics learning by incorporating cultural elements into an interactive Android application, improving both the feasibility and effectiveness of mathematics education for young learners.